2011
DOI: 10.1021/jo201263r
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of Transmetalation of Alkylboranes in Nickel-Catalyzed Alkyl–Alkyl Cross-Coupling Reactions

Abstract: Deuterium-labeled alkylborane reagents 2a and 2b were prepared and subjected to cross-coupling reactions in the presence of a nickel catalyst. NMR analysis of the products indicates that transmetalation from boron to nickel proceeds with retention of configuration. These results demonstrate that alkylnickel intermediates are configurationally stable under Suzuki cross-coupling conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
2
11
0
1
Order By: Relevance
“…73 In a recent report by our laboratory we have demonstrated that the same holds true for nickel-catalyzed cross-coupling reactions with alkyl halides (Scheme 22c). 74 …”
Section: Stereospecific Reactionsmentioning
confidence: 99%
“…73 In a recent report by our laboratory we have demonstrated that the same holds true for nickel-catalyzed cross-coupling reactions with alkyl halides (Scheme 22c). 74 …”
Section: Stereospecific Reactionsmentioning
confidence: 99%
“…36 Pd(0) could then undergo oxidative addition into the aziridinium moiety, and alkyl Au- to- Pd alkyl transmetalation 37 with retention of configuration (Pathway A) would provide palladacycle 11 . A stereochemically retentive transmetalation, which is typical for with Pd(II) with relatively nonpolar organometallic complexes such as trialkyl- 38 and pinacol-boronates 39 and alkyl mercury(II) complexes, 40 is expected due to the nonpolar nature of the C–Au bond. 41 A retentive C–C bond-forming reductive elimination 42 from Pd(II) intermediate 11 would have provided the expected 1,2- cis product 2a' .…”
Section: Resultsmentioning
confidence: 99%
“…Also in this case, 1 H NMR analysis of the reaction products confirmed the retentive nature of the transmetalation process under nickel(II) catalysis (Scheme 4 C). [9] In 2014 Morken and co-workers disclosed a similar mechanistic study for the Suzuki-Miyaura cross-coupling of 1,2-diboryl ester substrates. [10] Also in this case the palladium(0)-catalyzed coupling with vinyl halides was found to be retentive.…”
Section: The B!pdmentioning
confidence: 96%